Formulation of Problems for Stationary Dispersive Equations of Higher Orders on Bounded Intervals with General Boundary Conditions (Contemporary Mathematics, 2020)
Boundary value problems for linear stationary dispersive equations of order 2l + 1, l ∈ N with general linear boundary conditions have been considered on finite intervals (0, L). The existence and uniqueness of regular solutions have been established.
Keywords: stationary dispersive equations, general boundary conditions, regular solutions